The Relationship Between Median Age and Death Cases During the Coronavirus Disease 2019 (COVID-19) Pandemic: The Mediating Role of Current Health Expenditure - Kerem TOKER; Zekiye İrem GÖZÜBOL (Bezmiâlem Science, 2020)

(untitled)
Objective:This study aimed to identify and define the relationships among the median ages of countries, their death cases, and current health expenditures [percentage (%) of gross domestic product (GDP)] during the Coronavirus disease 2019 (COVID-19) pandemic.Methods:We analyzed the mediating role of current health expenditures (% of GDP) in the relationship between median age and death cases. Data from 60 countries with the highest COVID-19 cases were analyzed. Correlation and hierarchical regression tests were used in the analyses.Results:The effect of the median ages of countries on COVID-19 death cases was 27.5%, and on current health expenditures was 56.3%. When the effect of the median age and current health expenditure variables on death cases was analyzed together, the effect of the median age was statistically insignificant and the effect of current health expenditures was 35.4%.Conclusion:It was determined that current health expenditures have a positive mediating effect on the relationship between COVID-19 deaths and the median age of countries. It was determined that health expenditures did not make any strategic contribution to reducing mortality rates. The results provide an original theoretical framework for countries that aim to develop national health care management strategies.